Beetroot juice (Beta Vulgaris L) alternative handling of anemia in pregnancy - Zahrah Zakiyah; Dewi Setyaningsih (Jurnal Kesehatan Ibu dan Anak, 2019)
Iron deficiency anemia has become an important issue not only at the global level but even internationally. Iron supplementation is chosen as a solution to overcome iron deficiency anemia during pregnancy. The choice of iron as a solution has a negative effect because iron can initiate oxidative stress which is bad for health. The purpose of this study was to compare the effect of supplementing Fe and beetroot juice in the treatment of anemia in pregnant female rats. This research was an experimental study with a Randomized Posttest Only Control Group Design. The sample used was 20 pregnant female rats. The variables of this study were erythrocytes counts and hemoglobin levels. Statistical testing used the One-way ANOVA test. The mean of erythrocytes counted in the beetroot juice group of beetroot 3.6 gr /BW was able to compensate for the average of erythrocytes counts in the Fe supplementation group 1.08 mg/BW, followed by the group of 1.8g/BW beetroot juice. The average analysis of beetroot juice 3.6 gr/BW had no difference with the supplementation of Fe 1.08 mg/BW. This fact shows that the administration of 3.6 gr/BW beetroot juice was as effective as the supplementation of Fe 1.08 mg/BW in increasing hemoglobin levels. Beetroot juice was proven as an alternative product for handling anemia during pregnancy.